Use Of Graphic Medicine For Teaching Forensic Medicine To Undergraduate Medical Students: A Scoping Review (Journal of Forensic Medicine & Toxicology, 2026)
Background: Forensic medicine education is intellectually and emotionally demanding. Graphic medicine has gained attention in medical education, but its role in forensic medicine remains underexplored. Objective: To map the existing evidence on the use of graphic medicine in teaching forensic medicine to undergraduate medical students and to iden tify applications, outcomes, and knowledge gaps. Methods: A scoping review was conducted according to PRISMA-ScR guidelines. PubMed, Scopus, Web of Science, and Google Scholar were searched from 01 January 2010 to 31 March 2025. Studies describing or evaluating comics/graphic novels/graphic pathographies in undergraduate or postgraduate forensic medicine education were eligible. Study quality was assessed with the Medical Education Research Study Quality Instrument (MERSQI). Results: We included 26 studies in this review: 6 from forensic medicine and 20 from related high-emotion, procedure-heavy specialties (e.g., emergency medicine, trauma surgery). Four main themes appeared: 1. Graphic medicine simplifies complex forensic signs and procedures. 2. It helps learners develop empathy and narrative competence. 3. It supports ethical reasoning. 4. It strengthens emotional resilience. Evidence directly from forensic medicine is limited to small pilot studies and descriptive reports (average MERSQI qual ity score = 11.9 out of 18). Students reported higher engagement and better self-perceived understanding, but no ran domized controlled trials or long-term outcome data exist in forensic medicine. Conclusion: Graphic medicine (comics, graphic novels, and illustrated narratives) appears promising as a supplementary teaching tool in forensic medicine, espe cially for increasing student engagement and helping learners process emotional content. However, the evidence specific to forensic medicine remains early-stage and methodologically limited. High-quality comparative studies are required before it can be routinely recommended for widespread use
Keywords: Graphic medicine; Comics; Forensic medicine; Medical education; Empathy; Emotional resilience; Scoping review